2022
DOI: 10.3390/medicina58020301
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Serological Inflammatory Markers in Patients with Rotator Cuff Disease—A Systematic Review

Abstract: Background and Objectives: Rotator cuff disease (RCD) is a prominent musculoskeletal pain condition that spans a variety of pathologies. The etiology and precise diagnostic criteria of this condition remain unclear. The current practice of investigating the biochemical status of RCD is by conducting biopsy studies but their invasiveness is a major limitation. Recent biochemical studies on RCD demonstrate the potential application of serological tests for evaluating the disease which may benefit future clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…This leads to excess cellular apoptosis due to BNIP3 regulation, resulting in poor healing of the tendon [17]. In another study, the levels of HIF-1 and VEGF were found to be elevated in samples of rotator cuff tendon disease, and there was also a marked increase in the levels of MMPs, which promotes matrix degradation [54]. Mosca et al compared the levels of HIF-1α pre-and post-tendinopathy treatment and found that the levels of HIF-1α were increased in diseased tendons when compared to post-treatment and healthy tendons (Table 1) [55].…”
Section: Downregulatedmentioning
confidence: 99%
“…This leads to excess cellular apoptosis due to BNIP3 regulation, resulting in poor healing of the tendon [17]. In another study, the levels of HIF-1 and VEGF were found to be elevated in samples of rotator cuff tendon disease, and there was also a marked increase in the levels of MMPs, which promotes matrix degradation [54]. Mosca et al compared the levels of HIF-1α pre-and post-tendinopathy treatment and found that the levels of HIF-1α were increased in diseased tendons when compared to post-treatment and healthy tendons (Table 1) [55].…”
Section: Downregulatedmentioning
confidence: 99%
“…tendon integrity (13). Chi et al found that Vitamin B12, vitamin D and angiopoietin are significantly reduced in tendon disorders, which may contribute to a better understanding of the complex pathology of tendon disorders (54). High vitamin D level also promote bone health (55).…”
Section: B Amentioning
confidence: 99%
“…In summary, these studies have shown that pathological changes of RCRSP could be derived from intra-articular (synovial fluid) (Guan et al, 2020;Shih et al, 2018), extra-articular (RC and bursa) (Chillemi et al, 2016) and systemic inflammation (Savitskaya et al, 2011) (Figure 1). Two recent review articles summarised the functions and proposed new hypotheses of the involvement of VGEF, IL-1 β, IL-6, MMPs and other biomarkers in RCRSP (Lo, Leung, & Ngai, 2022;Lo, van Griensven, et al, 2022). IL-1β is an inflammatory mediator involved in tendinopathies (Mobasheri & Shakibaei, 2013;Tang et al, 2018), IL-6 regulates tendon healing and immune function (Andersen et al, 2011) and VEGF is a pro-inflammatory signal protein working for the formation of vascular tissue during tendon healing (Liu et al, 2021).…”
Section: Chemical Nociceptive Painmentioning
confidence: 99%
“…Two recent review articles summarised the functions and proposed new hypotheses of the involvement of VGEF, IL‐1 β, IL‐6, MMPs and other biomarkers in RCRSP (Lo, Leung, & Ngai, 2022; Lo, van Griensven, et al., 2022). IL‐1β is an inflammatory mediator involved in tendinopathies (Mobasheri & Shakibaei, 2013; Tang et al., 2018), IL‐6 regulates tendon healing and immune function (Andersen et al., 2011) and VEGF is a pro‐inflammatory signal protein working for the formation of vascular tissue during tendon healing (Liu et al., 2021).…”
Section: Research On Rcrsp Pain Naturementioning
confidence: 99%